2024
DOI: 10.1038/s41398-024-02833-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix abnormalities in the hippocampus of subjects with substance use disorder

Jake Valeri,
Charlotte Stiplosek,
Sinead M. O’Donovan
et al.

Abstract: Contextual triggers are significant factors contributing to relapse in substance use disorders (SUD). Emerging evidence points to a critical role of extracellular matrix (ECM) molecules as mediators of reward memories. Chondroitin sulfate proteoglycans (CSPGs) are a subset of ECM molecules that form perineuronal nets (PNN) around inhibitory neurons. PNNs restrict synaptic connections and help maintain synapses. Rodent models suggest that modulation of PNNs may strengthen contextual reward memories in SUD. Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…We also show here that stressed animals had an increased density of PNNs in the mPFC compared to controls. PNNs are extracellular matrix structures that play a key role in neuronal plasticity and enhance the activity of PV cells, and, in turn, cortical inhibitory activity 41 44 , 56 . Previous studies have shown that chronic stress increases the expression of PNNs and the activity of PV interneurons in the mPFC, and that these effects are associated with stress-induced behavioral deficits 34 , 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also show here that stressed animals had an increased density of PNNs in the mPFC compared to controls. PNNs are extracellular matrix structures that play a key role in neuronal plasticity and enhance the activity of PV cells, and, in turn, cortical inhibitory activity 41 44 , 56 . Previous studies have shown that chronic stress increases the expression of PNNs and the activity of PV interneurons in the mPFC, and that these effects are associated with stress-induced behavioral deficits 34 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this suggestion, it has been shown that chronic stress increases the number of parvalbumin GABA inhibitory interneurons (PV) 37 in the mPFC, and that increasing/decreasing the activity of PV cells or the expression of perineuronal nets (PNNs) in the mPFC reverses the behavioral deficits produced by stress 35 , 38 41 . PNNs are extracellular matrix structures that enhance the inhibitory activity of cortical PV cells 41 44 . Based on this evidence, in the current study we first determined whether ISD alters delay discounting behavior, and second, whether ISD changes cortical inhibitory function.…”
Section: Introductionmentioning
confidence: 99%
“…Increased densities of hippocampal PNNs, coupled with decreased ECM proteolytic genes and altered synaptic markers, support preclinical studies indicating that PNNs may stabilize reward memories. PNNs and ECM molecules may be promising targets for addressing cue-induced relapse in SUD [ 141 ]. In summary, PNN removal appears to create a blank slate for neuroplasticity that has the potential to combat drug-induced maladaptive plasticity and create new adaptive response, suggesting that targeting PNNs may be promising for the treatment of addiction.…”
Section: Roles Of Pnns In Memory-related Dysfunctionsmentioning
confidence: 99%
“…The rapid progress of PNN studies in a range of brain disease models highlights the prospects of PNN pharmacological targeting as a new medication approach [62,144,168,169]. Microscopy techniques may be highly instrumental in addressing PNN medical pharmacology both in terms of high-throughput drug lead screening and for the high-resolution investigation of drug targeting and effects at a single-synapse level.…”
Section: Perineuronal Net As a Potential Drug Targetmentioning
confidence: 99%